2018
DOI: 10.1111/wvn.12329
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Quality of Pediatric Randomized Controlled Trials Published in Both Nursing and Medical Journals: Adherence to the CONSORT Statement

Abstract: Background: Nursing care should be based on scientific evidence. However, studies must be performed rigorously with accurate reporting for their findings to be applicable to practice. Since the body of scientific nursing literature is broad, the quality and validity of its findings should be regularly controlled and verified to ensure their application and their practical impact.Purpose: To compare reporting quality of pediatric randomized controlled trial (RCT) articles in nursing and medical journals.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
8
0
4
Order By: Relevance
“…The reporting quality of RCTs is believed to be affected by some factors, such as sample size. A large and appropriate sample size is considered to be associated with better quality of RCT reporting [ 77 ]. In a previous study conducted by Kodounis et al [ 14 ], a significant association was found between sample size and the quality of reporting in a univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The reporting quality of RCTs is believed to be affected by some factors, such as sample size. A large and appropriate sample size is considered to be associated with better quality of RCT reporting [ 77 ]. In a previous study conducted by Kodounis et al [ 14 ], a significant association was found between sample size and the quality of reporting in a univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously Australian nurses relied more on surveys as their data collection method (Borbasi, Hawes, Wilkes, Stewart, & May, 2002) but there is a trend of increasing research quality and complexity (Wilkes & Jackson, 2011). Recently, paediatric nursing studies have been described as having the same scientific creditability and rigor as medical studies (Devos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with CONSORT has been studied in many medical fields with the general conclusion that reporting quality needs to be improved. [11][12][13][14][15][16][17] However, compliance with CONSORT of trials reported in OHS journals and the association to the RoB in studies has not been evaluated.…”
Section: Practicementioning
confidence: 99%